2021
DOI: 10.1002/andp.202100147
|View full text |Cite
|
Sign up to set email alerts
|

Optical Singularity Built on Tiny Holes

Abstract: Singular optics is a branch of modern optics, and it usually refers to various singularities including phase, polarization, and energy flux singularities. Lots of excellent researches in foundation and application fields relate to optical singularities. Nanotechnology enables the manipulation of optical singularities in nanometer scale. Metasurfaces consisting of nanoscatterers have aroused intensive interest in recent years because of the ultrathin structure and the powerful light manipulation ability. Optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 138 publications
(217 reference statements)
0
7
0
Order By: Relevance
“…[14][15][16][17][18][19][20] In comparison with the other methods, metasurface has natural advantages in miniaturization and integration of light field regulation, and it can cause spatially varying optical responses through the interaction between the light field and nanostructure instead of a spatial accumulation effect along an optical path. [21][22][23][24][25][26] Yang et al found that a high order plasmonic vortex generated by using multi-arm spiral nanoslits etched on metasurface carries a deuterogenic compound plasmonic vortex. [27] Zhou et al proposed a compound plasmonic vortex generator by using spiral nanoslits etched on metasurface to generate compound plasmonic vortices in active or passive modes.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] In comparison with the other methods, metasurface has natural advantages in miniaturization and integration of light field regulation, and it can cause spatially varying optical responses through the interaction between the light field and nanostructure instead of a spatial accumulation effect along an optical path. [21][22][23][24][25][26] Yang et al found that a high order plasmonic vortex generated by using multi-arm spiral nanoslits etched on metasurface carries a deuterogenic compound plasmonic vortex. [27] Zhou et al proposed a compound plasmonic vortex generator by using spiral nanoslits etched on metasurface to generate compound plasmonic vortices in active or passive modes.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, one accelerated beam can be produced with the help of spatial light modulator (SLM), [2,6,11,12] coupling grating, [13] microcavity, [14] or lens system. [15] Siviloglou G A et al generated DOI: 10.1002/andp.202200153 the 1D and 2D Airy beams using the SLM. [2] Zhang P et al obtained nonparaxial Mathieu and Weber accelerating beams also using the SLM.…”
Section: Introductionmentioning
confidence: 99%
“…Metasurfaces consisting of subwavelength unit array can effectively control the light field on nanometer scale, [15,16] and they have also been applied in the design of the planer devices like metalens, [17,18] metafilter, [19,20] circular polarizer, [21] and metahologram. [22,23] Metasurfaces are also utilized to generate accelerated beams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These elements are obviously difficult to integrate. Metasurface consisting of nanounits offers great potential for generating polarized beams, which is an efficient way to manipulate vector beams [24,25]. Due to the ultra-thin thickness, simple production, easy integration and light manipulation in nanometer scale, metasurfaces have been widely used in the design of optical elements, such as circular polarization analyzers [26,27], polarization converters [28,29], optical vortices [30,31].…”
Section: Introductionmentioning
confidence: 99%